Optimisation of Production Under Uncertainty The State-Contingent Approach - Rasmussen, Svend; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The book provides a short review of the classical approach to planning and decision making under uncertainty. It further explains the concept of state-contingent goods, and it extends earlier work on the state-contingent approach to describing production under uncertainty to the problems involved in optimising production under uncertainty.
Preface -- 1 Introduction -- 2 Decision Theory Elements -- 3 Utility Function -- 4 State-Contingent Outcome and Preference -- 5 Preferences and Subjective Probabilities -- 6 Formulation of the Decision Problem -- 7 Connections Between Input and State-Contingent Output -- 8 Optimising Production Under Uncertainty -- 9 Summary and Conclusion -- References.
Keywords: Economics; Microeconomics; Economics/Management Science; Microeconomics; Production/Logistics/Supply Chain Management; Economic Theory